2021
DOI: 10.15403/jgld-3504
|View full text |Cite
|
Sign up to set email alerts
|

Serum Visfatin as a Diagnostic Marker of Active Inflammatory Bowel Disease

Abstract: Background and Aims: Inflammatory bowel diseases (IBD) have been reported to be caused by a complex interplay of immunological, infectious, and genetic factors. Previous studies have suggested that adipokines play a role in IBD by inducing proinflammatory cytokines. We aimed to evaluate the role of visfatin in the diagnosis algorithm of active IBD. Methods: 85 newly diagnosed IBD patients [56 diagnosed with ulcerative colitis (UC) and 29 with Crohn‘s disease (CD)] and 30 healthy controls were included. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…Our data also support the previous observations that eNAMPT does not correlate with age and years of disease, while our correlation with hsCRP is supported by Saadoun et al ( 21 ), although other Authors failed to find this correlation. Our data is instead in line with Neubauer showing a correlation with IL-6 while we are the first to investigate and report a negative correlation with IL-10.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data also support the previous observations that eNAMPT does not correlate with age and years of disease, while our correlation with hsCRP is supported by Saadoun et al ( 21 ), although other Authors failed to find this correlation. Our data is instead in line with Neubauer showing a correlation with IL-6 while we are the first to investigate and report a negative correlation with IL-10.…”
Section: Discussionsupporting
confidence: 93%
“…Inflammatory bowel diseases (IBD) are a group of chronic inflammatory diseases (of which Crohn’s disease, CD, and ulcerative colitis, UC are the best known entities) whose etiology is not fully established, although genetic predisposition, environmental and dietary factors, alterations of the intestinal microbiome, increase of intestinal permeability, and a deficit of the innate immune response with excessive activation of the T-cell-mediated adaptive immune response are most likely involved ( 13 ). In these settings, a number of Authors have shown that serum eNAMPT levels are elevated ( 14 21 ). Briefly, serum eNAMPT is increased both in CD and in UC and it is likely to be correlated with the disease stage.…”
Section: Introductionmentioning
confidence: 99%
“…In CD patients, serum eNAMPT was elevated regardless of disease activity, whereas in UC patients, eNAMPT levels were significantly higher in patients with active disease as compared to inactive disease ( 66 , 174 , 175 ). Similar to the pattern observed in other inflammatory diseases, a positive correlation between the levels of eNAMPT and inflammation markers (e.g., IL-6, platelet count, erythrocyte sedimentation rate, or CRP) is apparent in IBD ( 173 , 174 ). Intriguingly, Colombo et al.…”
Section: Enampt In Diseasesupporting
confidence: 76%
“…A bulk of clinical studies in IBD reported elevated circulating eNAMPT levels in patients with ulcerative colitis (UC) and Crohn’s disease (CD) [ Table 2 ( 30 , 173 176 , 202 204 )]. Interestingly, eNAMPT levels were found to be differently associated with disease activity in UC and CD patients.…”
Section: Enampt In Diseasementioning
confidence: 99%
“…It was found to participate in the intra- and extracellular processes related to obesity [ 145 , 146 ]. Its higher serum expression was observed in the general population of IBD patients and their colonic samples [ 147 , 148 , 149 ]. Among pediatric IBD patients, visfatin correlated positively even with a disease activity assessed by biopsies [ 150 ].…”
Section: Other Adipokinesmentioning
confidence: 99%